Comparative Effects of Probiotics and Inactivated Cells of Saccharomyces cerevisiae Supplementations on Growth Performance, Feed Conversion Ratio and Some Blood Parameters in Quail (Coturnix japonica) - Hassan, Nazenine Othman (Sulaimani Journal for Pure and Applied Sciences, 2020)
In the recent years, the use of probiotics and prebiotics, as a food supplement, has been increased, it appears to be an effective supplement to reduce the use of antibiotics, coccidostats and mycotoxin binder, particularly in the poultry industry. The aims of the study were to investigate the effect of probiotic and prebiotic supplements on growth rate, feed conversion ratio and some blood parameters in Japanese quail. 150 quails were used, and randomly divided at day 3 of age into three equal groups: control groups; without any treatments, probiotic-treated group; treated with probiotic (0.150 g probiotic/l liter of water), and prebiotic-treated group; treated with (1 ml prebiotic/l liter of water) for 4 weeks. The resulted showed that total white blood cells, lymphocytes numbers, total red blood cells, hemoglobin concentration and total platelets were significantly (p≤0.05) increased in birds, treated with prebiotic when compared to the control and probiotic-treated group. While the granulocytes count, mean corpuscular volume, mean corpuscular hemoglobin and red blood cell distribution width-standard were significantly (p≤0.05) reduced in both prebiotic and probiotic-treated groups. The white blood mid cells number (monocytes, eosinophils, basophils and blasts cells) and mean corpuscular hemoglobin concentration were significantly increased in the prebiotic-treated birds compared to the control group. In addition, the pre-and probiotics were found to improve the level of serum-phosphor, blood sugar level, serum-creatinine. In conclusion, the prebiotic and probiotic supplementation appears to enhance red blood cell indices, and boost the immune system via the process of leukocytosis.
Keywords: blood biochemical parameters; Japanese quail; prebiotics; probiotics